FROM HR 4.0 TO BETTER SUPPLY CHAIN FLEXIBILITY: ROLE OF TALENT ON-BOARDING AND DEVELOPMENT IN THAILAND - Watthanabut, Busakorn (International Journal of Supply Chain Management, 2019)
Talent management is one of the most discussed areas of human resource management in 21st century. This is due to its vast range of implications in almost all processes of organization. However, introduction of HR 4.0 has diverted all the attention towards this new concept as talent management evolved in a more predicting role afterwards. This study has aimed to analyze the impact of talent management practices such as on-boarding, off-boarding and development on supply chain flexibility in mediating role of strategic HR 4.0 adoption. Responses were collected from the managerial employees of manufacturing sector of Thailand and those firms were selected for survey who were either adopted or in process of adoption of strategic HR 4.0. The gathered data was then tested statistically on SPSS and AMOS especially through confirmatory factor analysis and structural equation modeling. Results have revealed that talent management practices have significant impact on supply chain flexibility in manufacturing firms. Moreover, findings have also flagged strategic HR 4.0 adoption as a positive significant mediator in relationship between talent management practices and supply chain flexibility. Implications of this study has also extended towards telecommunication and service sectors too because most of such sectors are undergoing from strategic HR 4.0 adoption.